γδ T Lymphocytes in Asthma: a Complicated Picture - Zarobkiewicz, Michał K. (Arch Immunol Ther Exp (Warsz), 2021)
A minor subset (approximately 5%) of peripheral T cells has their TCR build up from γ and δ chains instead of α and β—those are the γδ T lymphocytes. They can be functionally divided into subsets, e.g., Th1-, Th2-, Th9-, Th17-, Tfh-, and Treg-like γδ T cells. They share some specifics of both innate and adaptive immunity, and are capable of rapid response to a range of stimuli, including some viral and bacterial infections. Atopic diseases, including asthma, are one of major health-related problems of modern western societies. Asthma is one of the most common airway diseases, affecting people of all ages and having potential life-threatening consequences. In this paper, we review the current knowledge about the involvement of γδ T cells in the pathogenesis of asthma and its exacerbations. We summarize both the studies performed on human subjects as well as on the murine model of asthma. γδ T cells seem to be involved in the pathogenesis of asthma, different subsets probably perform opposite functions, e.g., symptom-exacerbating Vγ1 and symptom-suppressing Vγ4 in mice model of asthma.